Expression, immunolocalization and processing of fertilins ADAM-1 and ADAM-2 in the boar (sus domesticus) spermatozoa during epididymal maturation - Bonet Sergi; Puigmulé Marta; Gatti Jean-Luc; Dacheux Jean-Louis; Guyonnet Benoît; Fàbrega Anna; Pinart Elisabeth (BMC, 2011)
Abstract Fertilin alpha (ADAM-1) and beta (ADAM-2) are integral membrane proteins of the ADAM family that form a fertilin complex involved in key steps of the sperm-oocyte membrane interaction. In the present work, we analyzed the presence of ADAM-1 and ADAM-2 mRNAs, the spermatozoa proteins' processing and their sub-cellular localization in epididymal samples from adult boars. ADAM-1 and ADAM-2 mRNAs were highly produced in the testis, but also in the vas efferens and the epididymis. On immunoblots of sperm extracts, ADAM-1 subunit appeared as a main reactive band of ~50-55 kDa corresponding to occurrence of different isoforms throughout the epididymal duct, especially in the corpus region where isoforms ranged from acidic to basic pI. In contrast, ADAM-2 was detected as several bands of ~90 kDa, ~75 kDa, ~50-55 kDa and ~40 kDa. The intensity of high molecular mass bands decreased progressively in the distal corpus where lower bands were also transiently observed, and only the ~40 kDa was observed in the cauda. The presence of bands of different molecular weights likely results from a proteolytic processing occurring mainly in the testis for ADAM-1, and also throughout the caput epididymis for ADAM-2. Immunolocalization showed that fertilin migrates from the acrosomal region to the acrosomal ridge during the sperm transit from the distal corpus to the proximal cauda. This migration is accompanied by an important change in the extractability of a part of ADAM-1 from the sperm membrane. This suggests that the fertilin surface migration may be triggered by the biochemical changes induced by the epididymal post-translational processing of both ADAM1 and ADAM-2. Different patterns of fertilin immunolocalization then define several populations of spermatozoa in the cauda epididymis. Characterization of such fertilin complex maturation patterns is an important step to develop fertility markers based on epididymal maturation of surface membrane proteins in domestic mammals.